THE INTENSITY OF THE HEAVY METALS BY TOPINAMBUR IN THE CONDITIONS OF THE OIL-POLLUTED AREAS - Lopushniak, V. I.; Hrytsuliak, H. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the ability of Jerusalem artichokes (Helianthus tuberous L.) to absorb heavy metals in an oil-contaminated ecosystem. The research was carried out in a territory of the oil and gas pipeline at the village of Bytkiv of Nadvirna district. Jerusalem artichokes were used for this study and planted on an area of 25 m2. The area of the experimental field in the village of Maidan of Tysmenytsia district (control option № 1). A total of eight treatments of the experiment with different rates of sewage sludge. It is established that the concentration of heavy metals in oil-contaminated soil and Jerusalem artichoke plants increases with increasing the amount of fertilizers in the soil. The maximum content of metals in the tested soils, green mass and Jerusalem artichoke roots was observed mainly in the variant of sewage sludge application at the rate of 40 t/ha and fertilizer N10P14K58.The green mass and roots of Jerusalem artichoke exhibited the highest content of heavy metals absorption the transition coefficients of metals in the system "roots - green mass" increase in the following : Pb → Co → Ni → Cd. The coefficients of biological absorption of metals by Jerusalem artichoke increase in a number of elements: Co → Ni → Ld → Ca. Where as The coefficients of biological accumulation of heavy metals with Jerusalem artichoke increase in a number of elements following series : L → Co → Ni → Ca. It is recommended to use Jerusalem artichoke as a phytoremediator of man-made areas.